2012
DOI: 10.1387/ijdb.113447sc
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of two novel members of the Mesp family in zebrafish

Abstract: Mesp proteins play crucial roles in the formation of heart, vasculature and somites during vertebrate embryogenesis. We have used phylogenetic and genomic analysis, combined with qRT-PCR and in situ hybridization, to characterize two novel additional mesp genes in zebrafish, mesp-ab and mesp-bb, and describe their expression pattern in wild type and segmentation mutants. Both mesp-ab and mesp-bb are expressed in early mesoderm with mesp-ab expression starting during late blastula stages and mesp-bb expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 46 publications
5
22
0
1
Order By: Relevance
“…Our data suggest that Tbx6 directly regulates the expression of both mesp-b paralogs in vivo (see also Kawamura et al, 2008;Cutty et al, 2012). Binding of Tbx6 to the mesp-b promoter and the functional relevance of this interaction have been demonstrated in other vertebrate models, including medaka (Terasaki et al, 2006), Xenopus (Tazumi et al, 2008) and mouse (Yasuhiko et al, , 2008, suggesting that this interaction is conserved.…”
Section: Molecular Interactions Between Tbx6 Mesp-b and Ripply1supporting
confidence: 56%
See 2 more Smart Citations
“…Our data suggest that Tbx6 directly regulates the expression of both mesp-b paralogs in vivo (see also Kawamura et al, 2008;Cutty et al, 2012). Binding of Tbx6 to the mesp-b promoter and the functional relevance of this interaction have been demonstrated in other vertebrate models, including medaka (Terasaki et al, 2006), Xenopus (Tazumi et al, 2008) and mouse (Yasuhiko et al, , 2008, suggesting that this interaction is conserved.…”
Section: Molecular Interactions Between Tbx6 Mesp-b and Ripply1supporting
confidence: 56%
“…We identified regions of Tbx6 binding in close proximity to the mesp-ba, mesp-bb and ripply1 genes ( Fig. 1F; supplementary material Table S1), many of which match those found computationally using the T-box consensus motif (Cutty et al, 2012). De novo motif discovery showed that the Tbx6…”
Section: Tbx6 Directly Regulates Mesp-b and Ripply1 Expressionmentioning
confidence: 67%
See 1 more Smart Citation
“…2), but that have conserved expression, regulation and function during vertebrate development (e.g. Cutty et al, 2012). As discussed further below, it has also been shown that functional regulatory elements are very flexible and the same gene expression outcome can be brought about by a non-conserved sequence.…”
Section: Box 2 Terminology and Methods For Identifying Conservationmentioning
confidence: 99%
“…The zebrafish has four Mesp genes, mespaa, mespab, mespba and mespbb, all of which are expressed in the anterior PSM during somitogenesis (Sawada et al, 2000;Durbin et al, 2000;Cutty et al, 2012). However, the roles of these Mesp genes in somitogenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%